A COMPARATIVE STUDY OF PHYSIOTHERAPY OUTCOMES BETWEEN INFRARED-TENS COMBINATION AND PNF THERAPIES IN NPH PATIENTS - Nasution, Sri Lestari Ramadhani; Ermi Girsang; Siti Aminah (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: The pain experienced by Nucleus Pulposus Herniation (NPH) patients can have an impact on productivity and may lead to disability. Therefore, non-pharmacological therapies can serve as alternatives in reducing pain levels for Grade I and Grade II NPH patients. Purpose: To compare the difference in effectiveness between Infrared-Transcutaneous Electrical Nerve Stimulation (IR-TENS) combination and Proprioceptive Neuromuscular Facilitation (PNF) therapies in reducing pain among NPH patients. Method: This research employed a quasi-experimental design with a two group before and after intervention conducted at the Physical Medicine and Rehabilitation Unit of Royal Prima Hospital in Medan. A total of 20 NPH patients were provided with interventions, consisting of a combination of IR and TENS therapies for 10 patients, and PNF therapy for the other 10 patients, administered eight times for one month. Pain measurement was conducted using a Visual Analogue Scale (VAS) questionnaire before and after the interventions. The statistical analysis employed an Independent Sample T test, with a significance level (α) set at 0.05. Result: There was a reduction in moderate and severe pain scales in both groups, and no subjects were experiencing severe pain anymore. However, the reduction in moderate pain scale was higher in the group receiving the combination of infrared and TENS therapies (80%) compared to the PNF therapy (70%). The Independent T test showed that there was no significant difference between the effectiveness of the combination of IR-TENS therapies and PNF therapy on pain in NPH patients (p-value = 0.075). Conclusion: Both groups of patients experienced a reduction in pain scale after the interventions, although there was no significant difference in the outcome between the two treatment groups. This implies that both therapies are equally effective in suppressing pain in NPH patients.